2020
DOI: 10.3389/fonc.2020.00032
|View full text |Cite
|
Sign up to set email alerts
|

Change of Pathological Type to Metaplastic Squamous Cell Carcinoma of the Breast During Disease Recurrence: Case Report and Literature Review

Abstract: Background: Metaplastic squamous cell carcinoma (SCC) of the breast is a rare and heterogeneous group of primary breast malignancies. The etiology, pathogenesis, and proper treatment for this kind rare breast cancer are still unclear. Case presentation: We reported a case of a 55-year-old woman with a palpable lump in the inner quadrant of the right breast. She underwent a right breast mass resection and sentinel lymph node biopsy, which revealed that the tumor was an invasive ductal carcinoma, followed by fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
(22 reference statements)
0
8
0
Order By: Relevance
“…Squamous cell metastasis to the breast from lung, stomach, and skin is more common than primary squamous carcinoma of the breast (2). Although it is primarily seen in post-menopausal women, it can be observed in other age groups as in our case (7,8). Squamous cell carcinomas of the breast have bigger than adenocarcinomas of the breast that can reach up to 10 cm in size (7,9).…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Squamous cell metastasis to the breast from lung, stomach, and skin is more common than primary squamous carcinoma of the breast (2). Although it is primarily seen in post-menopausal women, it can be observed in other age groups as in our case (7,8). Squamous cell carcinomas of the breast have bigger than adenocarcinomas of the breast that can reach up to 10 cm in size (7,9).…”
Section: Discussionmentioning
confidence: 60%
“…Although it is primarily seen in post-menopausal women, it can be observed in other age groups as in our case (7,8). Squamous cell carcinomas of the breast have bigger than adenocarcinomas of the breast that can reach up to 10 cm in size (7,9). Central cystic degeneration is common in tumors larger than 2 cm, and this cavity is filled with necrotic squamous debris (4).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In the case of our study, the remarkable observation was that there was a change in the molecular type during the treatment, namely, a conversion in HER2 status from negative to positive. We carefully reviewed previous studies and found that only a few of them mentioned changes in pathological types, 16 , 17 while none of these reports mentioned changes in molecular type. Miglietta et al highlighted that HER2 expression was highly unstable during disease evolution and reported that HER2 discordance was mostly driven by cases switching from HER2-negative to HER2-low.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the patient’s primary cancer was mixed small cell and SCC because of intratumoral heterogeneity or sampling artifacts. Guo et al 8 reported a case of a recurrent breast cancer whose pathological type changed from invasive ductal carcinoma to metaplastic SCC. The authors’ hypothesis was that the tumor’s transformation into breast SCC was likely to be the result of the malignant transformation of breast cancer stem/progenitor cells.…”
Section: Discussionmentioning
confidence: 99%